DEVELOPING CRITICAL THINKING AND CYBERSECURITY LITERACY SKILLS AHEAD OF THE 2024 ELECTION FOR STUDENTS AT VOCATIONAL HIGH SCHOOL OF AL BADAR IN TULUNGAGUNG - Mubah, A. Safril; Anabarja, Sarah; Yakti, Probo Darono; Pratamasari, Annisa (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
The spread of information in the digital media tends to include fake news. Ahead of the 2024 election, hoax is distributed for the certain political interests and can affect divided societies. As the novice voters who are familiar with social media, high school students become the hoax target. Therefore, a training for developing chritical thinking skill and cybersecurity literacy is required by the novice voters. The target of this training is students of Al Badar Vocational High School in Tulungagung. It aims at giving the students a skill for thinking critically towards any information. The authors organized this activity by analyzing the training needs for students, giving a critical thinking training and evaluating the training result. The authors found that the students’ level of critical thinking skill is still low. Therefore, the authors suggest the novice voters to critically check and cross-check all information.